Emotional processing and therapeutic change in depression: A case study - Pinheiro, Patrícia (2018)
The association between clients' higher capability of emotional processing and good therapeutic outcome has been consistently observed in different therapeutic approaches. Despite previous studies that have reported an association between emotional processing and pre- to posttherapy change in symptoms, the session-by-session relation between emotional processing and therapeutic change needs further research. The current study explored, in a good-outcome case of depression, the session-by-session longitudinal association of the level of emotional processing with (a) clinical symptoms and (b) type of emotions aroused (adaptive or maladaptive). Using a time-series analysis, we observed a strong negative association between the intensity of clinical symptoms and the level of emotional processing in the same session, r = -.71, p < .001, but a nonsignificant association between emotional processing and the symptoms in the preceding session, r = -.37, p = .101, and the next session, r = -.29, p = .180. During the increase in the level of emotional processing, we observed a change in the type of emotions aroused, from maladaptive to more adaptive. The results support that emotional processing is associated with therapeutic change, although not necessarily precedes such change, at least from one session to the next. As it is an exploratory study, the results must be interpreted carefully. (PsycINFO Database Record